2015
DOI: 10.1002/mus.24889
|View full text |Cite
|
Sign up to set email alerts
|

Balance and coordination training, but not endurance training, enhances synaptophysin and neurotrophin‐3 immunoreactivity in the lumbar spinal cord after sciatic nerve crush

Abstract: BCT can positively affect spinal cord plasticity after a (PNI), and these modifications are important in the rehabilitation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 60 publications
(144 reference statements)
0
10
0
Order By: Relevance
“…60 Therefore, in the SC-EX group, treadmill exercise may have increased BDNF and NT3 expression in motor neurons and reconnected motor neurons with primary afferent neurons. Bonetti et al 23 In contrast, the synaptic coverage of VGLUT1-IR terminals in the MSC-EX group was not significantly different from that in the MSC group. Using a rat sciatic nerve transection and repair model, Brandt et al 14 showed that the synaptic coverage of VGLUT1-IR terminals was significantly lower when the timing of exercise initiation after injury was delayed (started 21-28 days after injury) than when exercise was started early (3 days after injury).…”
Section: Differences In Spinal Changes After Different Number Of Crus...mentioning
confidence: 86%
See 4 more Smart Citations
“…60 Therefore, in the SC-EX group, treadmill exercise may have increased BDNF and NT3 expression in motor neurons and reconnected motor neurons with primary afferent neurons. Bonetti et al 23 In contrast, the synaptic coverage of VGLUT1-IR terminals in the MSC-EX group was not significantly different from that in the MSC group. Using a rat sciatic nerve transection and repair model, Brandt et al 14 showed that the synaptic coverage of VGLUT1-IR terminals was significantly lower when the timing of exercise initiation after injury was delayed (started 21-28 days after injury) than when exercise was started early (3 days after injury).…”
Section: Differences In Spinal Changes After Different Number Of Crus...mentioning
confidence: 86%
“…Therefore, in the SC‐EX group, treadmill exercise may have increased BDNF and NT3 expression in motor neurons and reconnected motor neurons with primary afferent neurons. Bonetti et al 23 conducted a 4‐week treadmill exercise or balance coordination training on a rat sciatic nerve crush model, and reported that balance coordination training resulted in higher NT‐3 expression in the spinal cord. Different types of exercise may have different effects on the plasticity of the spinal cord after sciatic nerve injury.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations